Ibm Edukasi Kesehatan Teknik Akupresur untuk Mengurangi Nyeri Haid pada Remaja - Masruroh; Cahyaningrum; Widayati; Hapsari Windayanti (UNIVERSITAS NGUDI WALUYO, 2023)
Menstrual pain is pain that occurs in the lower abdomen experienced by women before menstruation and during menstruation without accompanied by signs of pathology and cramps usually occur. The problem of menstrual pain in adolescents if not handled properly will interfere with adolescent activities. Menstrual pain can be overcome with non-pharmacological techniques, one of which is the acupressure technique. Acupressure is a therapy that is given by giving massage or pressing certain points on the body. Acupressure therapy is widely used by the community to treat primary dysmenorrhea. Acupressure has a fairly high success rate with little or no complications if the disorder is only functional, the diagnosis is correct, the technique is good and the prognosis is probable. In addition, acupressure is also easy to do at a low cost. The activity of providing information about acupressure techniques to reduce menstrual pain was carried out at the Temanggung Swadaya Vocational School. The number of students who took part in the activity was 38 students. The prestest results showed that most of the students had sufficient knowledge about a number of acupressure techniques to reduce menstrual pain by 55.3%. The results of the posttest showed that most of the students had knowledge in the good category at 81.6%. Socialization of the practice of acupressure techniques to reduce menstrual pain is very important because it is one way to reduce menstrual pain, so it is necessary to conduct health education on acupressure techniques to reduce menstrual pain. Suggestions to the Temanggung Swadaya Vocational School to work together with health workers so that they can provide continuous health problem counseling to students of Temanggung Swadaya Vocational Schools ABSTRAK Nyeri haid adalah nyeri yang terjadi pada perut bagian bawah yang dialami oleh wanita sebelum menstruasi maupun selama menstruasi tanpa disertai tanda patologi dan biasanya terjadi kram . Masalah nyeri haid pada remaja kalua tidak ditangani dengan tepat akan menggangu aktivitas remaja. Nyeri haid dapat diatasi dengan teknik non farmokologi salah satunya adalah dengan teknik Akupresur. Akupresur adalah terapi yang diberikan dengan cara memberikan pemijatan atau penekanan titik tertentu pada tubuh. Terapi akupresur banyak digunakan oleh masyarakat untuk mengatasi dismenore primer. Akupresur memiliki angka keberhasilan cukup tinggi dengan sedikit atau tanpa komplikasi jika kelainan hanya bersifat fungsional, diagnosa tepat, teknik baik serta prognosa yang memungkinkan. Selain itu, akupresur juga mudah dilakukan dengan biaya yang murah. Kegiatan pemberian informasi tentang teknik akupresur untuk mengurangi nyeri haid di laksanakan di SMK Swadaya Temanggung. Jumlah siswa yang mengikuti kegiatan sebanyak 38 siswa. Hasil prestest didapatkan sebagian besar siswi mempunyai pengetahuan cukup tentang sebanyak teknik akupresur untuk mengurangi nyeri haid sebanyak 55,3%. Hasil posttest didapatkan sebagian besar siswi mempunyai pengetahuan dalam kategori baik sebesar 81,6%. Sosialisasi praktik teknik akupresur untuk mengurangi nyeri haid sangatlah penting karena merupakan salah satu cara untuk mengurangi nyeri haid , sehingga perlu dilakukan pendidikan kesehatan teknik akupresur untuk mengurangi nyeri haid. Saran kepada Pihak SMK Swadaya Temanggung supaya bekerjasama keapada pihak tenaga kesehatan supaya dapat memberikan penyuluah masalah kesehatan secara kontinyu kepada para siswa siswa SMK Swadaya Temanggung